Glue coating as well as preparation method and application thereof

By applying a glue coating composed of water, organic solvent, coating glue, dispersant and anti-shrinkage agent on the current collector ear of the aqueous battery, the corrosion problem caused by electrolyte precipitation is solved, and the cycle life of the battery is significantly improved and tensile strength, suitable for a variety of electrolytes.

CN119242125APending Publication Date: 2025-01-03CHAOWEI POWER GROUP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411328083.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

After the water-based battery is charged and discharged for a long time, the electrolyte precipitates in the electrolyte at the pole ear of the current collector, resulting in corrosion of the current collector, reduced battery capacity and attenuation of the cycle life.

Method used

Using a glue coating, the preparation method includes a combination of water, organic solvent, coating glue, dispersant and anti-shrinkage agent, to form a dense coating by vacuum defoaming and drying, and to apply to the pole of the current collector. To block the contact between the electrolyte and the current collector and prevent corrosion.

Benefits of technology

It effectively suppresses the corrosion of the current collector, improves the tensile strength, extends the cycle life of water-based batteries, and is suitable for water-based batteries with different components of electrolytes, with a cycle life of more than twice that of traditional batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242125A_ABST
    Figure CN119242125A_ABST
Patent Text Reader

Abstract

The invention discloses a glue coating layer as well as a preparation method and application thereof, belongs to the technical field of aqueous batteries, and solves the problems of current collector corrosion, battery capacity reduction and cycle life attenuation caused by electrolyte precipitation in electrolyte at a tab of a current collector of an aqueous battery in the prior art. The preparation raw materials of the glue coating comprise water, an organic solvent, a coating glue, a dispersing agent and an anti-shrinking agent. The adhesive coating layer provided by the invention has insulativity and excellent corrosion resistance, and the adhesive coating layer is applied to the tab of the current collector, so that the corrosion of the current collector can be inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aqueous batteries, and in particular to a glue coating and a preparation method and application thereof. Background Art

[0002] In practical applications, after a long period of cyclic charge and discharge, electrolytes in the electrolyte will precipitate out at the lugs of the current collector, which can easily cause current collector corrosion, increased ohmic polarization of the pole piece, reduced battery capacity, and decreased cycle life. Therefore, how to avoid such phenomena and improve the overall electrochemical performance of aqueous batteries has become an urgent problem to be solved. Summary of the invention

[0003] In view of the above situation, the present invention aims to provide a glue coating and its preparation method and application, which are used to solve one of the problems of electrolyte precipitation in the electrolyte at the pole ear of the current collector of the existing aqueous battery, causing corrosion of the current collector, reduced battery capacity and shortened cycle life.

[0004] The purpose of the present invention is mainly achieved through the following technical solutions:

[0005] The invention provides an adhesive coating. The raw materials for preparing the adhesive coating include water, an organic solvent, a coating adhesive, a dispersant and an anti-shrinkage agent.

[0006] Furthermore, the organic solvent is one or more of N-methyl-2-pyrrolidone, N,N-dimethylformamide, triol, n-hexane, tetrahydrofuran, hydroxypyridine and acetonitrile.

[0007] Furthermore, the coating adhesive is one or more of ABS plastic adhesive, polyacrylic resin, epoxy resin, polyvinyl chloride, organic silicone adhesive, polyvinyl acetate emulsion and VAE emulsion.

[0008] Furthermore, the dispersant is one or more of water glass, sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, triethylhexyl phosphoric acid, sodium lauryl sulfate, methylpentyl alcohol, polyacrylamide, fatty acid polyethylene glycol ester and cellulose derivatives.

[0009] Furthermore, the anti-shrinkage agent is one or more of polypropylene oxide, inorganic vehicle ethylene glycol and monoglyceride.

[0010] Furthermore, the volume ratio of water to the organic solvent is 0.01 to 1:1.

[0011] Furthermore, the mass of the dispersant is 2% to 10% of the mass of the coating rubber.

[0012] The present invention also provides a method for preparing the above-mentioned adhesive coating, comprising the following steps:

[0013] S1, mixing water and an organic solvent to obtain a solution A;

[0014] S2, adding the coating glue to solution A and mixing to obtain solution B;

[0015] S3, adding a dispersant and an anti-shrinkage agent to solution B in sequence and mixing to obtain solution C;

[0016] S4, subjecting solution C to vacuum degassing, coating, and drying to obtain a glue coating.

[0017] The present invention also provides an application of the above-mentioned adhesive coating, wherein the above-mentioned adhesive coating is applied to a coating current collector.

[0018] Furthermore, the coated current collector includes a current collector substrate and a pole ear arranged on the current collector substrate, and a glue coating is provided on the surface of the pole ear.

[0019] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0020] a) The adhesive coating of the present invention has insulation and excellent corrosion resistance. The adhesive coating is applied to the electrode ear of the current collector, which can block the direct contact between the electrolyte and the current collector inside the coating, avoid the exchange of electrons between the conductive particles in the electrolyte and the current collector, and thus inhibit the corrosion of the current collector. The electrode ear of the coated current collector is provided with an adhesive coating, and the conduction of electrons occurs inside the current collector, which will not cause the ohmic resistance of the current collector part in the battery to increase, and has no inhibitory effect on the cycle performance of the battery.

[0021] b) In the preparation method of the adhesive coating of the present invention, the coating adhesive can be combined with water molecules and organic solvent molecules by intermolecular forces in microscopic form; by first adding a dispersant, the coating adhesive can be effectively dispersed so that it is evenly distributed in solution B, and then adding an anti-shrinkage agent, in the subsequent drying process, it is possible to ensure that the tension of solution C is equal everywhere, so that the coating adhesive can form a more uniform film.

[0022] c) In the preparation method of the coated current collector of the present invention, the glue solution is subjected to vacuum degassing treatment to prevent air from being mixed into the glue solution during the preparation process, and to prevent air from causing incomplete subsequent drying and film formation of the glue solution when the glue solution is coated on the electrode ear of the current collector, and the current collector is exposed and corroded by salt creep.

[0023] d) In the preparation method of the coated current collector of the present invention, by adding an appropriate amount of dispersant, the glue liquid can be effectively and evenly dispersed, and a glue coating with uniform thickness and density can be prepared when preparing the coated current collector, and it can be firmly attached to the surface of the collector's pole ear, effectively enhancing the tensile strength at the collector's pole ear, making it not easy to break; by adding a trace amount of anti-shrinkage agent, the glue liquid can be effectively prevented from excessively shrinking during the pre-drying and drying process of the collector, causing deformation and damage to the collector.

[0024] e) The current collector of the present invention is a new type of coated current collector with conductive middle layer and insulating outer layer. Compared with the traditional current collector, it has higher tensile strength and can effectively inhibit the salt climbing phenomenon of the electrolyte, alleviate the corrosion of the current collector, and extend the cycle life of the aqueous battery; for example, the tensile strength of the tab of the coated current collector of the present invention can reach more than 6.5N, such as 6.58~14N, which is more than 1.3 times the tensile strength of the traditional current collector without glue coating. The coated current collector of the present invention is suitable for aqueous batteries with electrolytes of different components and has strong adaptability.

[0025] f) The cycle life of the aqueous battery of the present invention is long, which is more than twice that of the conventional battery without a gel-coated current collector.

[0026] Other features and advantages of the present invention will be described in the following description, and part of them will become obvious from the description, or will be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the contents particularly pointed out in the written description and the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0028] Figure 1 is a macroscopic photograph of the coated current collector;

[0029] Figure 2 is a comparison diagram of the current collectors of Example 1 of the present invention and Comparative Example 1;

[0030] Figure 3 is a comparison diagram of the tensile strength of the current collector tabs of Example 1 of the present invention and Comparative Example 1;

[0031] Figure 4 is a comparison diagram of the salt creep of the current collector after battery cycling between Example 1 of the present invention and Comparative Example 1;

[0032] Figure 5 1 is a cycle performance diagram of an aqueous sodium ion battery assembled in Example 1 of the present invention and Comparative Example 1;

[0033] Figure 6 is a comparison diagram of the current collectors of Example 2 of the present invention and Comparative Example 2;

[0034] Figure 7 This is a comparison chart of the tensile strength of the current collector tabs of Example 2 of the present invention and Comparative Example 2;

[0035] Figure 8 This is a comparison diagram of the salt creep of the current collector after battery cycling between Example 2 of the present invention and Comparative Example 2;

[0036] Fig. 9 It is a cycle performance diagram of the aqueous zinc ion battery assembled by Example 2 of the present invention and Comparative Example 2. DETAILED DESCRIPTION

[0037] Preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used to explain the principles of the present invention together with the embodiments of the present invention.

[0038] The invention provides an adhesive coating. The raw materials for preparing the adhesive coating include water, an organic solvent, a coating adhesive, a dispersant and an anti-shrinkage agent.

[0039] Specifically, in order to prevent contamination by impurities, deionized water may be used.

[0040] Specifically, the organic solvent may be one or more of N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), triol, n-hexane, tetrahydrofuran (THF), hydroxypyridine and acetonitrile. For example, the organic solvent may be DMF and hydroxypyridine, and the volume ratio of DMF to hydroxypyridine is 0.8 to 1.5:1.

[0041] Specifically, the coating adhesive can be one or more of ABS plastic adhesive, polyacrylic resin, epoxy resin, polyvinyl chloride, organic silicone adhesive, polyvinyl acetate emulsion and VAE emulsion. For example, the coating adhesive can be epoxy resin and VAE emulsion, and the mass ratio of epoxy resin to VAE emulsion is 1.5-2.5:3.

[0042] Specifically, the dispersant may be one or more of water glass, sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, triethylhexyl phosphoric acid, sodium lauryl sulfate, methylpentyl alcohol, polyacrylamide, fatty acid polyethylene glycol esters, and cellulose derivatives. For example, the dispersant may be water glass and sodium pyrophosphate, and the mass ratio of water glass to sodium pyrophosphate is 0.8 to 1.5:2.

[0043] Specifically, the anti-shrinkage agent may be one or more of polypropylene oxide, inorganic vehicle ethylene glycol and monoglyceride.

[0044] Specifically, the role of water is to prevent the solvent from evaporating too quickly during the drying process, causing some adhesive coatings to shrink. Excessive use of water will result in low solute concentration, increased fluidity, and uneven film formation; too little water will result in low solvent content, too fast solvent evaporation rate, and greater stress when the coating is dried. Therefore, the volume ratio of water to organic solvent is controlled to be (0.01-1):1, such as 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, preferably (0.1-0.5):1.

[0045] Specifically, too much coating glue can easily lead to a solution that is too viscous, difficult to apply, and prone to produce large stress when drying. Too little coating glue can lead to a thinner solution that is also difficult to apply, takes a long time to dry, and has a poor film-forming effect.

[0046] Specifically, considering that too much dispersant mass can easily cause the glue coating to be loose, causing small solvent molecules in the electrolyte to enter the glue layer and directly contact the current collector, thereby corroding the current collector. Too little dispersant mass cannot achieve a good dispersion effect, resulting in uneven film formation of the coating. Therefore, the mass of the dispersant is controlled to be 2% to 10% of the mass of the coating glue, such as 3%, 5%, 7%, 9%; preferably 3% to 7%.

[0047] Specifically, considering that too much anti-shrinkage agent is easy to release the internal stress of the adhesive layer, causing the bond energy between the adhesive layer molecules to become weak, and it is difficult to form a dense coating; too little anti-shrinkage agent leads to excessive stress in the adhesive layer, and the tab shrinks seriously. Therefore, the weight of the anti-shrinkage agent is controlled to be 0.05% to 2% of the coating glue weight, such as 0.1%, 0.12%, 0.15%, 0.17%, 0.19%; preferably 0.1% to 1%.

[0048] Specifically, the adhesive coating has good insulation, compactness, and corrosion resistance, and can block direct contact between the electrolyte and the current collector inside the coating, avoiding electron exchange between the conductive particles in the electrolyte and the current collector, thereby inhibiting corrosion of the current collector.

[0049] The present invention also provides a method for preparing a glue coating, comprising the following steps:

[0050] S1, mixing water and an organic solvent to obtain a solution A;

[0051] S2, adding the coating glue to solution A, stirring and diluting until the mixture is uniform, to obtain solution B;

[0052] S3, adding the dispersant and the anti-shrinkage agent to the solution B in sequence, stirring and dissolving, to obtain a solution C;

[0053] S4, subjecting solution C to vacuum degassing, coating, and drying to obtain a glue coating.

[0054] Specifically, in the above S1, the role of water is to prevent the solvent from evaporating too quickly during the subsequent drying process, causing some adhesive coatings to shrink. Excessive use of water will result in a low solute concentration in solution C, increased fluidity, and uneven film formation; too little water will result in a low solvent content in solution C, a too fast solvent evaporation rate, and greater stress when the coating is dried. Therefore, the volume ratio of water to organic solvent is controlled to be (0.01-1):1, such as 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, preferably (0.1-0.5):1.

[0055] Specifically, in the above S1, too high a stirring speed can easily cause the solution to splash, resulting in changes in the solution concentration, and too low a stirring speed can make it difficult to disperse the solute, resulting in insufficient solute dissolution or too long a stirring time, and low production efficiency. Therefore, the stirring speed is controlled to be 50 to 300 r / min, such as 80 r / min, 100 r / min, 130 r / min, 150 r / min, 180 r / min, 200 r / min, 230 r / min, 250 r / min, 280 r / min; preferably 100 to 260 r / min.

[0056] Specifically, in the above S2, too much coating glue will easily cause the solution to be too viscous, making it difficult to apply, and will easily generate large stress during drying, causing deformation of the collector tab. Too little coating glue will result in a thinner solution, making it difficult to apply, taking a long time for the solution to dry, and having a poor film-forming effect. Therefore, the volume ratio of the coating glue mass to solution A is controlled to be 1g: (1-10)mL, such as 1g: 2mL, 1g: 5mL, 1g: 7mL, 1g: 9mL; preferably 1g: (2-8)mL.

[0057] Specifically, in the above S3, it is considered that too much dispersant will easily cause the adhesive layer to be loose, and too little dispersant will not achieve a good dispersion effect, resulting in uneven film formation of the coating. Therefore, the mass of the dispersant is controlled to be 2% to 10% of the mass of the coating adhesive, such as 3%, 5%, 7%, 9%; preferably 3% to 7%.

[0058] Specifically, in the above S3, considering that too much anti-shrinkage agent is easy to release the internal stress of the adhesive layer, causing the bond energy between the adhesive layer molecules to become weak, and it is difficult to form a dense coating; too little anti-shrinkage agent leads to excessive stress in the adhesive layer. Therefore, the weight of the anti-shrinkage agent is controlled to be 0.05% to 2% of the coating adhesive weight, such as 0.1%, 0.12%, 0.15%, 0.17%, 0.19%; preferably 0.1% to 1%.

[0059] Specifically, in the above S4, considering that the vacuum degree is too large, the boiling point of the solution is too low, and the solution will boil violently during degassing; if the vacuum degree is too small, the tiny bubbles in the solution cannot be completely removed, and the tiny bubbles will form cavities after subsequent coating and drying. Therefore, the vacuum degree is controlled to be 900-960kPa, such as 920kPa, 930kPa, 950kPa; preferably 900-940kPa, (one standard atmospheric pressure is 1MPa, 1MPa=1000kPa).

[0060] Specifically, in the above S4, it is considered that if the vacuum degassing treatment time is too long, the solution may boil and the solvent may evaporate too quickly; if the vacuum degassing treatment time is too short, it may be difficult to discharge the tiny bubbles in the solution. Therefore, the vacuum degassing treatment time is controlled to be 2 to 15 minutes, such as 5 minutes, 7 minutes, 10 minutes, or 12 minutes; preferably 3 to 12 minutes.

[0061] It should be noted that in the above preparation method, the coating adhesive can combine with water molecules and organic solvent molecules by intermolecular forces in the microscopic form; the dispersant is first added to effectively disperse the coating adhesive so that it is evenly distributed in solution B, and then the anti-shrinkage agent is added. In the subsequent drying process, the tension of solution C can be guaranteed to be equal everywhere, so that the coating adhesive can form a more uniform film.

[0062] The present invention also provides an application of the above-mentioned adhesive coating, wherein the above-mentioned adhesive coating is applied to a coating current collector.

[0063] Specifically, the present invention provides a coating current collector comprising the above-mentioned glue coating, such as Figure 1 As shown, the coated current collector includes a current collector substrate and a pole ear arranged on the current collector substrate, and the surface of the pole ear is provided with the above-mentioned glue coating. The raw materials for preparing the glue coating include water, organic solvent, coating glue, dispersant and anti-shrinkage agent.

[0064] Specifically, the adhesive coating is arranged on 30% to 80% of the lower surface of the tab, that is, the adhesive coating is arranged along the end of the tab connected to the collector matrix in a direction away from the collector matrix, and the area of ​​the adhesive coating accounts for 30% to 80% of the area of ​​the tab.

[0065] Specifically, in order to prevent contamination by impurities, deionized water may be used.

[0066] Specifically, the thickness of the adhesive coating is 5 to 200 μm, preferably 10 to 100 μm.

[0067] The present invention also provides a method for preparing the above-mentioned coating current collector, comprising the following steps:

[0068] Step 1, mixing water and an organic solvent to obtain solution A;

[0069] Step 2, adding the coating glue to solution A and mixing to obtain solution B;

[0070] Step 3, adding a dispersant and an anti-shrinkage agent to solution B in sequence and mixing them to obtain solution C;

[0071] Step 4, subjecting solution C to vacuum degassing treatment;

[0072] Step 5: coating solution C on the lower end surface of the electrode ear of the current collector; and then drying to obtain a coated current collector.

[0073] Specifically, in the above step 1, the role of water is to prevent the subsequent current collector from evaporating too quickly during the drying process, causing some glue coatings to shrink, resulting in deformation and damage to the current collector. Excessive use of water will lead to a low solute concentration in solution C, increased fluidity, and uneven film formation on the surface of the current collector; too little water will cause a low solvent content in solution C, a too fast solvent evaporation rate, and a large stress when the coating of the current collector is dried, causing the pole ear to deform and shrink. Therefore, the volume ratio of water to organic solvent is controlled to be (0.01-1):1, such as 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, preferably (0.1-0.5):1.

[0074] Specifically, in the above step 1, if the stirring speed is too high, it is easy to cause the solution to splash, resulting in changes in the solution concentration, and if the stirring speed is too low, it is difficult to disperse the solute, resulting in insufficient solute dissolution or too long stirring time, and low production efficiency. Therefore, the stirring speed is controlled to be 50 to 300 r / min, such as 80 r / min, 100 r / min, 130 r / min, 150 r / min, 180 r / min, 200 r / min, 230 r / min, 250 r / min, 280 r / min; preferably 100 to 260 r / min.

[0075] Specifically, in the above step 2, too much coating glue will easily cause the solution to be too viscous, making it difficult to coat, and will easily generate large stress during drying, causing deformation of the collector tab. Too little coating glue will result in a thinner solution, making it difficult to coat, taking a long time for the solution to dry, and having a poor film-forming effect. Therefore, the volume ratio of the coating glue mass to solution A is controlled to be 1g: (1-10) mL, for example, 1g: 2 mL, 1g: 5 mL, 1g: 7 mL, 1g: 9 mL; preferably 1g: (2-8) mL. It should be noted that the volume ratio of the coating glue mass to solution A here only represents the proportional relationship between the two. During the production process, the amount of the two can be determined according to actual needs.

[0076] Specifically, in the above step 3, considering that too much mass of the dispersant may cause the glue layer to be loose, small solvent molecules in the electrolyte may enter the glue layer and directly contact the current collector, thereby corroding the current collector. Too little mass of the dispersant cannot achieve a good dispersion effect, resulting in uneven film formation of the coating. Therefore, the mass of the dispersant is controlled to be 2% to 10% of the mass of the coating glue, such as 3%, 5%, 7%, 9%; preferably 3% to 7%.

[0077] Specifically, in the above step 3, it is considered that too much anti-shrinkage agent will easily release the internal stress of the adhesive layer, causing the bond energy between the adhesive layer molecules to become weak, and it is difficult to form a dense coating; too little anti-shrinkage agent will cause excessive stress in the adhesive layer and serious inward shrinkage of the tab. Therefore, the mass of the anti-shrinkage agent is controlled to be 0.05% to 2% of the mass of the coating adhesive, such as 0.1%, 0.12%, 0.15%, 0.17%, 0.19%; preferably 0.1% to 1%.

[0078] Specifically, in the above step 4, considering that the vacuum degree is too large, the boiling point of the solution is too low, and the solution will boil violently during degassing; if the vacuum degree is too small, the tiny bubbles in the solution cannot be completely removed, and after subsequent coating and drying, the tiny bubbles will form cavities, thereby providing channels for the contact between the solvent molecules and the current collector. Therefore, the vacuum degree is controlled to be 900-960kPa, such as 920kPa, 930kPa, 950kPa; preferably 900-940kPa, (one standard atmospheric pressure is 1MPa, 1MPa=1000kPa).

[0079] Specifically, in the above step 4, it is considered that if the vacuum degassing time is too long, the solution may boil and the solvent may evaporate too quickly; if the vacuum degassing time is too short, it may be difficult to discharge the tiny bubbles in the solution. Therefore, the vacuum degassing time is controlled to be 2 to 15 minutes, such as 5 minutes, 7 minutes, 10 minutes, or 12 minutes; preferably 3 to 12 minutes.

[0080] Specifically, in the above step 5, the current collector can be one or more of Al foil, Cu foil, Zn foil, Mg foil, stainless steel foil, stainless steel mesh, Ni mesh, Ti foil, Ti mesh, carbon paper, carbon cloth and graphite paper.

[0081] Specifically, in the above step 5, the current collector can be designed into various shapes and sizes according to actual needs.

[0082] Specifically, in the above step 5, the current collector can be pre-cut by a cutting machine to cut the current collector tab portion according to actual needs.

[0083] Specifically, in the above step 5, the tab cutting work is completed by unwinding the current collector at the front end, cutting it with a cutting machine, and rewinding it at the rear end.

[0084] Specifically, in the above step 5, both surfaces of the lower end of the tab need to be coated, and the side surfaces of the tab coated with the adhesive coating need to be sealed with the adhesive layer.

[0085] Specifically, in the above step 5, a spray gun can be used to seal the side of the tab with a glue layer. The spray gun spray speed is controlled to be 1 to 5 μL / mm 2 For example, 2μL / mm 2 、3μL / mm 2 , 4μL / mm 2 .

[0086] Specifically, in the above step 5, coating can be applied to one side first and then to the other side; specifically comprising the following steps:

[0087] Step 5: Flatten the current collector and evenly coat the solution C on the lower side of the current collector tab;

[0088] Step 6, pre-drying the current collector;

[0089] Step 7, turn over the pre-dried current collector, repeat step 5, and ensure that the coated front and back positions overlap;

[0090] Step 8: Repeat the pre-drying operation in step 6, and then increase the temperature for drying;

[0091] Step 9: seal the side of the current collector pole ear with a glue layer and dry it, wherein the sealed portion of the side of the coated current collector pole ear is the side of the pole ear coated with the coating, to obtain a coated current collector.

[0092] Specifically, in the above step 5, the current collector can be spread on a flat and clean glass plate, and solution C can be evenly coated on 30% to 80% of the lower surface of the current collector tab, such as 40%, 50%, 60%, 70%; preferably 50% to 70%.

[0093] Specifically, in the above step 6, if the pre-drying temperature is too high, it is easy to cause the solution to form a film too quickly, and the internal stress cannot be released in time, causing the ear of the collector to deform; if the pre-drying temperature is too low, the solution will not be completely dried. When the back is subsequently coated, the solution on the front will adhere to the glass plate, causing coating damage. If the pre-drying time is too long, the production efficiency will be low; if the pre-drying time is too short, the solution cannot be well filmed. Therefore, the pre-drying temperature is controlled to be 30-90°C, for example, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C; preferably 35-70°C; the pre-drying time is 0.5-5min, for example, 1min, 2min, 3min, 4min; preferably 0.5-3min.

[0094] Specifically, in the above step 8, if the drying temperature is too high, it is easy to cause oxidation of the current collector, too fast evaporation of the solvent, and uneven coating. If the drying temperature is too low, the coating cannot be completely dried. If the drying time is too long, it is easy to cause the coating glue on the surface of the coating to self-solidify, making it difficult for the internal solvent to evaporate and the coating to dry. If the drying time is too short, it is easy to cause incomplete drying of the solution or poor film formation of the coating. Therefore, the drying temperature is controlled to be higher than the pre-drying temperature, for example, the drying temperature is 60 to 200°C, for example, 70°C, 80°C, 90°C, 100°C, 120°C, 150°C, 170°C, 180°C, 190°C; preferably 60 to 150°C; the drying time is 2 to 10min, for example, 3min, 4min, 5min, 6min, 7min, 8min, 9min; preferably 3 to 8min.

[0095] Specifically, in the above step 9, the solution C in step 5 is used to seal the side of the current collector tab with a glue layer.

[0096] Specifically, in the above step 9, a spray gun can be used to seal the side of the current collector tab with a glue layer. Considering that the spray speed of the spray gun is too high, the impact force of the solution is too large, causing damage to the current collector; if the spray speed is too low, it is easy to cause the solution to fall in a parabolic curve, so that the sprayed solution cannot be accurately sprayed to the tab position. If the spraying time is too long, it is easy to cause the solution to be affected by gravity after the side coating, resulting in uneven film thickness; if the spraying time is too short, it cannot be guaranteed that the side is completely covered by the coating, and there is a risk of current collector leakage. Therefore, the solution spray speed of the spray gun is controlled to be 1-5μL / mm 2 For example, 2μL / mm 2 、3μL / mm 2 , 4μL / mm 2 .

[0097] Specifically, in the above step 5, the coating can be performed on both sides simultaneously by a coating machine; specifically comprising the following steps:

[0098] S501, evenly coating solution C on both sides of the lower end of the current collector tab;

[0099] S502, drying the current collector;

[0100] S503, sealing the side of the current collector electrode tab with a glue layer and drying the side, wherein the sealed portion of the side of the coated current collector electrode tab is the electrode tab side coated with the coating, to obtain a coated current collector.

[0101] Specifically, in the above S502, if the drying temperature is too high, it is easy to cause oxidation of the current collector, too fast evaporation of the solvent, and uneven coating. If the drying temperature is too low, the coating cannot be completely dried. If the drying time is too long, it is easy to cause the coating glue on the surface of the coating to self-solidify, making it difficult for the internal solvent to evaporate and the coating to dry. If the drying time is too short, it is easy to cause incomplete drying of the solution or poor film formation of the coating. Therefore, the drying temperature is controlled to be 60 to 200°C, for example, 70°C, 80°C, 90°C, 100°C, 120°C, 150°C, 170°C, 180°C, 190°C; preferably 60 to 150°C.

[0102] Specifically, in the above S503, a spray gun can be used to seal the side of the current collector with a glue layer. Considering that the spray speed of the spray gun is too high, the impact force of the solution is too large, causing damage to the current collector; if the spray speed is too low, it is easy to cause the solution to fall in a parabolic curve, so that the sprayed solution cannot be accurately sprayed to the position of the pole ear. If the spraying time is too long, it is easy to cause the solution to be affected by gravity after the side coating, resulting in uneven film thickness; if the spraying time is too short, it cannot be guaranteed that the side is completely covered by the coating, and there is a risk of leakage of the current collector. Therefore, the solution spray speed of the spray gun is controlled to be 1-5μL / mm 2 For example, 2μL / mm 2 、3μL / mm 2 , 4μL / mm 2 .

[0103] The present invention also provides an aqueous battery, which comprises the above-mentioned coating current collector.

[0104] Specifically, the aqueous battery can be a new type of aqueous secondary battery such as an aqueous lithium-ion battery, an aqueous sodium-ion battery, an aqueous zinc-ion battery, an aqueous aluminum-ion battery, a zinc-nickel secondary battery, a supercapacitor, an aqueous nickel-bismuth battery, and an aqueous zinc-air battery.

[0105] The adhesive coating of the present invention has insulation and excellent corrosion resistance. The adhesive coating is applied to the pole ear of the current collector to block the direct contact between the electrolyte and the current collector inside the coating, and avoid the exchange of electrons between the conductive particles in the electrolyte and the current collector, thereby inhibiting the corrosion of the current collector. The pole ear of the coated current collector is provided with an adhesive coating, and the conduction of electrons occurs inside the current collector, which will not cause the ohmic resistance of the current collector part in the battery to increase, and has no inhibitory effect on the cycle performance of the battery.

[0106] In the preparation method of the coated current collector of the present invention, the glue solution is subjected to vacuum degassing treatment to prevent air from being mixed into the glue solution during the preparation process, and to prevent air from causing incomplete subsequent drying and film formation of the glue solution when the electrode ear of the current collector is coated, and the current collector is exposed and corroded by salt creep.

[0107] In the preparation method of the coated current collector of the present invention, by adding an appropriate amount of dispersant, the glue liquid can be effectively and evenly dispersed, and a coating with uniform thickness and density can be prepared when preparing the coated current collector, and it can be firmly attached to the surface of the collector's pole ear, effectively enhancing the tensile strength at the collector's pole ear, making it less likely to break; by adding a trace amount of anti-shrinkage agent, the glue liquid can be effectively prevented from excessively shrinking during the pre-drying and drying process of the current collector, causing deformation and damage to the current collector.

[0108] The coating current collector prepared by the present invention is a new type of coating current collector with conductive middle layer and insulating outer layer. Compared with the traditional current collector, it has higher tensile strength, can effectively inhibit the salt climbing phenomenon of electrolyte, alleviate the corrosion of the current collector, and extend the cycle life of the aqueous battery; for example, the tensile strength of the pole ear of the coating current collector of the present invention can reach more than 6.5N, such as 6.58~14N, which is more than 1.3 times the tensile strength of the traditional current collector without glue coating, such as 1.3~2.5 times. The coating current collector of the present invention is suitable for aqueous batteries with electrolytes of different components and has strong adaptability.

[0109] The aqueous battery of the present invention has a long cycle life, for example, the cycle life of the aqueous battery of the present invention reaches more than 200 cycles, which is more than twice, for example, 2 to 6 times, of the conventional battery without a gel-coated current collector. The capacity retention rate of the aqueous battery is more than 88%, for example, 88.84% to 92%.

[0110] The technical solution of the present invention is further explained below in conjunction with specific embodiments.

[0111] Embodiment 1

[0112] This embodiment provides a glue coating and its application in a coating current collector, wherein the application process includes a preparation process of the glue coating.

[0113] like Figure 1 As shown, the coated current collector includes a current collector substrate and a pole ear arranged on the current collector substrate, and a glue coating is provided on the surface of the pole ear. The raw materials for preparing the glue coating include water, an organic solvent, a coating glue, a dispersant and an anti-shrinkage agent.

[0114] The method for preparing the coating current collector of this embodiment comprises the following steps:

[0115] 1. Take 2 mL of deionized water and 10 mL of DMF and place them in container cc. Add a magnetic stirrer at a speed of 180 r / min to obtain solution A.

[0116] 2. Weigh 3g of ABS plastic glue and add it to solution A, stir and dilute until mixed evenly to obtain solution B;

[0117] 3. Weigh 0.15 g of sodium tripolyphosphate as a dispersant and 0.006 g of polypropylene oxide as an anti-shrinkage agent, respectively, and add them to solution B in sequence. Stir and dissolve them to obtain solution C.

[0118] 4. Place solution C in a vacuum tank and perform vacuum degassing at a vacuum degree of 920 kPa for 6 minutes;

[0119] 5. According to the requirements of aqueous sodium-ion batteries, select Al foil as the current collector and cut it into a suitable shape and size;

[0120] 6. Place the Al foil current collector on a flat and clean glass plate, and use a pipette to evenly apply 100 μL of solution C on 70% of the surface of the lower end of the current collector tab;

[0121] 7. Pre-dry the Al foil current collector at 50°C for 2 minutes;

[0122] 8. Turn over the pre-dried Al foil current collector and repeat step 6, making sure that the front and back sides of the glue coating overlap;

[0123] 9. Repeat the pre-drying operation of step 7 for the Al foil current collector, then raise the temperature to 100°C and keep it at this temperature for 6 minutes for drying;

[0124] 10. Overlap multiple Al foil current collectors, spray solution C at a rate of 3 μL / mm2 through a spray gun, so as to seal the sides of the tabs of the coated current collector with glue, and dry them at 100°C for 6 minutes, wherein the sealed side of the tabs of the coated current collector is the tab side with coating, and finally obtain the coated Al foil current collector. The thickness of the glue coating in this embodiment is 20 μm.

[0125] This embodiment also provides an aqueous battery, which includes the above-mentioned coated Al foil current collector. According to the selected coated Al foil current collector, electrode sheet preparation, diaphragm cutting, electrolyte preparation and other operations of the aqueous sodium ion battery are performed, wherein lithium manganese oxide is used as the positive electrode, sodium titanium phosphate is used as the negative electrode, non-woven fabric is used as the diaphragm, and an appropriate amount of 2M CH3COOLi+1M CH3COONa solution is injected as the electrolyte, and the aqueous sodium ion battery is assembled by controlling the N / P ratio of the positive and negative electrodes, and the electrochemical performance of the aqueous sodium ion battery is characterized.

[0126] Comparative Example 1:

[0127] Except that the Al foil current collector is not treated in any way, the assembly and testing methods of the other aqueous sodium ion batteries are the same as those in Example 1.

[0128] Embodiment 2

[0129] This embodiment provides a glue coating and its application in a coating current collector, wherein the application process includes a preparation process of the glue coating.

[0130] The coated current collector comprises a current collector substrate and a pole ear arranged on the current collector substrate. The surface of the pole ear is provided with a glue coating. The raw materials for preparing the glue coating include water, an organic solvent, a coating glue, a dispersant and an anti-shrinkage agent.

[0131] The method for preparing the coating current collector of this embodiment comprises the following steps:

[0132] 1. Take 3 mL of deionized water and 12 mL of DMF and place them in a container. Add a magnetic stirrer at a speed of 120 r / min to obtain solution A.

[0133] 2. Weigh 2.5 g of polyvinyl acetate emulsion and add it to solution A, stir and dilute until mixed evenly to obtain solution B;

[0134] 3. Weigh 0.075 g of sodium dodecyl sulfate as a dispersant and 0.0125 g of monoglyceride as an anti-shrinkage agent, respectively, and add them to solution B in sequence. Stir and dissolve to obtain solution C.

[0135] 4. Place solution C in a vacuum tank and perform vacuum degassing at a vacuum degree of 910 kPa for 10 minutes;

[0136] 5. According to the requirements of aqueous zinc-ion batteries, select Zn foil as the current collector and cut it into appropriate shape and size;

[0137] 6. Place the Zn foil current collector on a flat and clean glass plate, and use a pipette to evenly apply 80 μL of solution C on 60% of the surface of the lower end of the current collector tab;

[0138] 7. Pre-dry the Zn foil current collector at 60°C for 1 min;

[0139] 8. Turn over the pre-dried Zn foil current collector and repeat step 6, making sure that the front and back sides of the glue coating overlap;

[0140] 9. Repeat the pre-drying operation of step 7 for the Zn foil current collector, then raise the temperature to 140°C and keep it for 4 minutes for drying.

[0141] 10. Overlap multiple Zn foil current collectors, spray solution C at a rate of 5 μL / mm2 through a spray gun to seal the sides of the coated current collectors with a glue layer, and dry them at 140°C for 4 minutes, wherein the sealed side of the coated current collector is the side of the electrode ear with the coating, and finally obtain a coated Zn foil current collector. The thickness of the glue coating in this embodiment is 40 μm.

[0142] This embodiment also provides an aqueous battery, which includes the above-mentioned coated Zn foil current collector. According to the selected coated Zn foil current collector, electrode sheet preparation, diaphragm cutting, electrolyte preparation and other operations of the aqueous zinc ion battery are performed, wherein MnO2 is used as the positive electrode, Zn powder is used as the negative electrode, glass fiber is used as the diaphragm, and an appropriate amount of 1.5M ZnSO4 solution is injected as the electrolyte, and the aqueous zinc ion battery is assembled by controlling the N / P ratio of the positive and negative electrodes, and the electrochemical performance of the aqueous zinc ion battery is characterized.

[0143] Comparative Example 2:

[0144] Except that the Zn foil current collector is not treated in any way, the rest of the assembly and testing methods of the aqueous zinc ion battery are the same as those of Example 2.

[0145] Embodiment three:

[0146] This embodiment provides a glue coating and its application in a coating current collector, wherein the application process includes a preparation process of the glue coating.

[0147] The coated current collector comprises a current collector substrate and a pole ear arranged on the current collector substrate. The surface of the pole ear is provided with a glue coating. The raw materials for preparing the glue coating include water, an organic solvent, a coating glue, a dispersant and an anti-shrinkage agent.

[0148] The method for preparing the coating current collector of this embodiment comprises the following steps:

[0149] 1. Take 1 mL of deionized water, 5 mL of DMF and 5 mL of hydroxypyridine and place them in a container. Add a magnetic stirrer at a speed of 240 r / min to obtain solution A.

[0150] 2. Weigh 1.5 g of polyvinyl chloride and add it to solution A, stir and dilute until the mixture is evenly mixed to obtain solution B;

[0151] 3. Weigh 0.03 g of water glass and 0.06 g of sodium pyrophosphate as dispersants and 0.0135 g of inorganic medium ethylene glycol as an anti-shrinkage agent, respectively, and add them to solution B in sequence, stir and dissolve to obtain solution C;

[0152] 4. Place solution C in a vacuum tank and perform vacuum degassing at a vacuum degree of 930 kPa for 12 minutes;

[0153] 5. According to the requirements of aqueous aluminum ion batteries, select Ni foil as the current collector and cut it into a suitable shape and size;

[0154] 6. Evenly apply solution C on 50% of the surface of both sides of the lower end of the current collector tab;

[0155] 7. Dry the Ni foil current collector at 120° C. for 8 min to obtain a coated Ni foil current collector;

[0156] 8. Overlap multiple Ni foil current collectors, spray solution C at a rate of 2 μL / mm2 through a spray gun to seal the sides of the coated current collectors with a glue layer, and dry them at 120°C for 8 minutes, wherein the sealed side of the coated current collector is the side of the electrode ear with the coating, and finally obtain a coated Ni foil current collector. The thickness of the glue coating in this embodiment is 50 μm.

[0157] This embodiment also provides an aqueous battery, which includes the above-mentioned coated Ni foil current collector. According to the selected coated Ni foil current collector, the electrode sheet preparation, diaphragm cutting, electrolyte preparation and other operations of the aqueous aluminum ion battery are performed, wherein LiV3O8 is used as the positive electrode, Al / CNTs is used as the negative electrode, cellulose is used as the diaphragm, and an appropriate amount of 3M Al(OTF)3 solution is injected as the electrolyte. By controlling the N / P ratio of the positive and negative electrodes, the aqueous aluminum ion battery is assembled, and the electrochemical performance of the aqueous sodium ion battery is characterized.

[0158] Comparative Example 3:

[0159] Except that the Ni foil current collector is not treated in any way, the assembly and testing methods of the other aqueous aluminum ion batteries are the same as those of Example 3.

[0160] Embodiment 4:

[0161] This embodiment provides a glue coating and its application in a coating current collector, wherein the application process includes a preparation process of the glue coating.

[0162] The coated current collector comprises a current collector substrate and a pole ear arranged on the current collector substrate. The surface of the pole ear is provided with a glue coating. The raw materials for preparing the glue coating include water, an organic solvent, a coating glue, a dispersant and an anti-shrinkage agent.

[0163] The method for preparing the coating current collector of this embodiment comprises the following steps:

[0164] 1. Take 2 mL of deionized water, 2 mL of isopropanol and 6 mL of acetonitrile and place them in a container. Add a magnetic stirrer at a speed of 150 r / min to obtain solution A.

[0165] 2. Weigh 2g of epoxy resin and 3g of VAE emulsion, add them to solution A, stir and dilute until mixed evenly, to obtain solution B;

[0166] 3. Weigh 0.2 g of fatty acid polyethylene glycol ester as a dispersant and 0.035 g of methyl glycerol as an anti-shrinkage agent, respectively, and add them to solution B in sequence, stir and dissolve to obtain solution C;

[0167] 4. Place solution C in a vacuum tank and perform vacuum degassing at a vacuum degree of 940 kPa for 3 minutes;

[0168] 5. Select graphite paper as the current collector and cut it into the appropriate shape and size;

[0169] 6. Place the graphite paper current collector on a flat and clean glass plate, and use a pipette to evenly apply 50 μL of solution C on 65% of the surface of the lower end of the current collector tab;

[0170] 7. Pre-dry the graphite paper current collector at 40°C for 1 min;

[0171] 8. Turn over the pre-dried graphite paper current collector, repeat step 6, and ensure that the front and back sides of the glue coating overlap;

[0172] 9. Repeat the pre-drying operation of step 7 for the graphite paper current collector, then raise the temperature to 80° C. and keep it warm for 5 minutes to dry it, to obtain a coated graphite paper current collector.

[0173] 10. Overlap multiple graphite paper current collectors, spray solution C at a rate of 1 μL / mm2 through a spray gun, so as to seal the sides of the coated current collectors with a glue layer, and dry them at 80°C for 5 minutes, wherein the sealed side of the coated current collector is the side of the electrode ear with the coating, and finally obtain a coated graphite paper current collector. The thickness of the glue coating in this embodiment is 30 μm.

[0174] This embodiment also provides an aqueous battery, which includes the above-mentioned coated graphite paper current collector. According to the selected coated graphite paper current collector, the electrode sheet of the supercapacitor is prepared, the diaphragm is cut, the electrolyte is prepared, etc., wherein NiCo LDH is used as the positive electrode, AC is used as the negative electrode, and glass fiber is used as the diaphragm. An appropriate amount of 6M KOH solution is injected as the electrolyte, and the supercapacitor is assembled by controlling the N / P ratio of the positive and negative electrodes, and the electrochemical performance of the supercapacitor is characterized.

[0175] Comparative Example 4:

[0176] Except that the graphite paper current collector is not treated in any way, the rest of the supercapacitor assembly and testing methods are the same as those in Example 4.

[0177] The tensile strength of the current collector tabs of the embodiments and comparative examples are shown in Table 1 below. It can be seen that the current collector tabs of the present invention have high tensile strength, the current collector of the present invention has no obvious salt creep after the battery of the present invention is cycled, and the cycle life of the battery of the present invention is long.

[0178] Table 1 Current collector tab tensile strength and battery performance of the embodiments and comparative examples

[0179]

[0180]

[0181] Figure 2 1 is a comparison diagram of the current collectors of Example 1 of the present invention and Comparative Example 1. The left side is the coating current collector of Example 1, and the right side is the current collector of Comparative Example 1.

[0182] Figure 3 3 is a comparison chart of the tensile strength of the current collector tabs of Example 1 of the present invention and Comparative Example 1. It can be seen that the tensile strength of the current collector tabs of Example 1 is higher than that of Comparative Example 1.

[0183] Figure 4 1 is a comparison diagram of the salt creep of the current collector after battery cycling between Example 1 of the present invention and Comparative Example 1; the left side is Example 1 and the right side is Comparative Example 1; it can be seen that there is no obvious salt creep in Example 1.

[0184] Figure 5 It is a cycle performance diagram of the aqueous sodium ion battery assembled in Example 1 of the present invention and Comparative Example 1.

[0185] Figure 6 1 is a comparison diagram of the current collectors of Example 2 and Comparative Example 2 of the present invention, wherein the left side is the coated current collector of Example 2, and the right side is the current collector of Comparative Example 2.

[0186] Figure 7 3 is a comparison chart of the tensile strength of the current collector tabs of Example 2 of the present invention and Comparative Example 2. It can be seen that the tensile strength of the current collector tabs of Example 2 is higher than that of Comparative Example 2.

[0187] Figure 8 1 is a comparison diagram of the salt creep of the current collector after battery cycling between Example 2 of the present invention and Comparative Example 2; the left side is Example 2, and the right side is Comparative Example 2; it can be seen that there is no obvious salt creep in Example 2.

[0188] Fig. 9 It is a cycle performance diagram of the aqueous zinc ion battery assembled by Example 2 of the present invention and Comparative Example 2.

[0189] The inventors have conducted a large number of experimental studies during the research process, and now list some solutions with poor performance as comparative examples as follows.

[0190] Comparative Example 5

[0191] This comparative example provides a coating current collector. The preparation method of the coating current collector is the same as that of Example 1, except that, in step 2, 15 g of polyvinyl acetate emulsion is weighed.

[0192] Comparative Example 6

[0193] This comparative example provides a coating current collector. The preparation method of the coating current collector is the same as that of Example 1, except that in step 3, 0.9 g of sodium dodecyl sulfate is weighed as a dispersant.

[0194] Comparative Example 7

[0195] This comparative example provides a coating current collector. The preparation method of the coating current collector is the same as that of Example 1, except that in step 3, 0.5 g of monoglyceride is weighed as an anti-shrinkage agent.

[0196] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A rubber coating, characterized in that: The raw materials for preparing the adhesive coating include water, an organic solvent, a coating adhesive, a dispersant and an anti-shrinkage agent.

2. The adhesive coating according to claim 1, characterized in that: The organic solvent is one or more of N-methyl-2-pyrrolidone, N,N-dimethylformamide, triol, n-hexane, tetrahydrofuran, hydroxypyridine and acetonitrile.

3. The adhesive coating according to claim 1, characterized in that: The coating adhesive is one or more of ABS plastic adhesive, polyacrylic resin, epoxy resin, polyvinyl chloride, organic silicone adhesive, polyvinyl acetate emulsion and VAE emulsion.

4. The adhesive coating according to claim 1, characterized in that: The dispersant is one or more of water glass, sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, triethylhexyl phosphoric acid, sodium lauryl sulfate, methyl amyl alcohol, polyacrylamide, fatty acid polyethylene glycol ester and cellulose derivatives.

5. The adhesive coating according to claim 1, characterized in that: The anti-shrinkage agent is one or more of polypropylene oxide, inorganic vehicle ethylene glycol and monoglyceride.

6. The adhesive coating according to claim 1, characterized in that: The volume ratio of water to the organic solvent is 0.01 to 1:

1.

7. The adhesive coating according to claim 1, characterized in that: The mass of the dispersant is 2% to 10% of the mass of the coating rubber.

8. A method for preparing a rubber coating according to any one of claims 1 to 7, characterized in that: The steps include: S1, mixing water and an organic solvent to obtain a solution A; S2, adding the coating glue to solution A and mixing to obtain solution B; S3, adding a dispersant and an anti-shrinkage agent to solution B in sequence and mixing to obtain solution C; S4, subjecting solution C to vacuum degassing, coating, and drying to obtain a glue coating.

9. An application of a rubber coating, characterized in that: The adhesive coating according to any one of claims 1 to 7 or the adhesive coating prepared by the preparation method according to claim 8 is applied to a coating current collector.

10. The use of the adhesive coating according to claim 9, characterized in that: The coated current collector comprises a current collector substrate and a pole ear arranged on the current collector substrate, and a glue coating is arranged on the surface of the pole ear.

Citation Information

Patent Citations

  • Electricity storage device and method for producing same

    CN103891029A

  • Lithium ion battery insulating coating, preparation method and pole piece and lithium ion battery using insulating coating

    CN104449011A

  • Polymer insulating coating and preparation method thereof

    CN115377609A

  • High-flexibility lithium ion battery positive electrode tab insulating coating and preparation method thereof

    CN117832773A

  • Current collector assembly with insulating coating, pole piece, preparation method and application

    CN118399031A